Building the Character of a Religious Young Generation - Diovany Tirtana; Anis Turmudhi; Eka Yuliyanti (Trescode Green Organization, 2024)
This activity aims to improve the religiosity of the younger generation in Gedawang Village, Banyumanik, Semarang City, by providing character development based on religious values. This program is expected to equip the younger generation with a strong moral foundation, so that they are able to avoid negative behavior and become role models in society. Data were collected through interviews with participants and local community leaders, and analyzed qualitatively to assess the impact of the program. The results showed a significant increase in the understanding and application of religious values ​​among participants. The younger generation showed more positive changes in attitudes, such as increased discipline, honesty, and participation in religious activities. Community leaders also reported improvements in behavior and increased social involvement among the younger generation. This program makes an important contribution to the character development of the younger generation by providing an effective model to improve their religiosity and morality. The findings of this program can be used as a basis for the development of similar policies and programs in other areas, in order to create a younger generation that is based on strong religious and moral values, and contributes positively to society.